Rates and profiles of self-harm presenting to Malaysian general hospitals: data from the Ministry of Health in 2011 - Masiran, Ruziana; Haniff, Jamaiyah; Ali, Nor Hayati; Abdul Hamid, Abdul Muneer (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Self-harm is an important global health concern as it is a strong predictor and risk factor for completed suicide. This paper is aimed to estimate the incidence rate of self-harm and to describe the profiles of people who self-harmed in 2011. Methods: This is a descriptive study based on secondary data retrieved from the Ministry of Health (MOH) of Malaysia hospitals’ discharge records from the 1st of January to 31st of December 2011. Results: The overall self-harm rate was 16.6 per 100 000 population (n= 4 815). Adults in the state of Johor had the highest rate of self-harm. There were more female self-harmers within the peak age group of 20-29 years. Indians, Muslims and those who were unmarried had the highest rates of self-harm. Male mostly used unspecified chemical (45.89%) while female used non-opioid analgesics (24.79%). Conclusions: In 2011, the rate of self-harm was 16.6 per 100 000 population with slightly higher rate observed among adult females compared to males and twice as high among girls than boys. Less lethal methods of self-harm were employed.